Partisipasi Masyarakat Dalam Implementasi Program Kota Tanpa Kumuh (KOTAKU) di Kawasan Kota Lama Kelurahan Tirtasiak Kecamatan Payung Sekaki Kota Pekanbaru - Reza Pirziliya; Yoskar Kadarisman (Jurnal Ilmiah Wahana Pendidikan, 2023)
Program a slum management platform called Kota Tanpa Kumuh (KOTAKU) aims to improve infrastructure access so that a livable, productive, and sustainable community may be built. The community in the target location serves as the primary actor in the Kotaku program, which is a participatory development initiative. This study was carried out in Kota Pekanbaru, Kecamatan Payung Sekaki, Kelurahan Tirtasiak, and Kawasan Kota Lama. This study's goal was to examine the community's involvement in the Kota Tanpa Kumuh (KOTAKU) Program's implementation from each of its four participation stages, namely the planning, implementation, monitoring, and use stages. Identifying the elements that affect community engagement is another objective. With 77 respondents in all, this study used a descriptive quantitative methodology. According to the study's findings, community involvement is low during the planning, implementation, and monitoring phases, but high during the utilization phase. The level of community involvement is generally considered to be medium. The community's awareness or comprehension of the Kotaku Program has the biggest impact on participation.